The legal understanding of intentional medical error - Totić Mirza (Medicinski Glasnik Specijalne Bolnice za Bolesti Štitaste Žlezde i Bolesti Metabolizma "Zlatibor", 2017)
The paper is devoted to doctor, a professional and humanist who dedicated himself to medicine and is committed to lifelong learning, ethics and assistance to victims, even against their express consent. The theme is focused on the problem of intentional medical error in order to negate it in the context that the conscientious doctors should be protected from tort and free of moral burden. This paper seeks to answer the question, if the error represents a doctor's failure to the detriment of the user (patient), how should we treat his attempt, made professionally and with the best intentions, regardless of the fatal outcome? In addition, medical-legal theory and practice beside intentional medical mistake mention also the unintentional, whose formation does not require any kind of responsibility because the doctor's behavior in that case was not inconsistent with medical ethics, standards and rules. In this regard, the author's research was based on the following questions: is there a deliberate medical error, who is ready to knowingly endanger the patient by doing medical procedures contrary to the rules (neglect, avoidance of assistance, misdiagnosis, improper treatment, indifference, discrimination), who is competent to qualify the taken action as an error (intentional, unintentional) and what evidences are required for the brutal attack on the integrity of top experts, that will be charged and prosecuted? Literature abounds with assertions that medical errors are as old as medicine, which is not true. Also, it is incorrect to say that it had appeared for the first time in the middle of the nineteenth century. That would be a roughly canceling of ancient medical marking, bearing in mind that even before the mentioned period, there had been a very successful medicine with high quality doctors and their brilliant achievements, but also with illnesses and dead persons. As far the data on the exact occurrence of medical errors are considered, the numerous authors claim that it does not have to be communicated, since it is placed in the field of history, that unlike many science is not exact, and should not always be considered as reliable. Any medical error makes a multiple interests, firstly of the researchers in the true sense of the word, and secondly, of the sensationalist columnists. The latter see the culprit only in the doctor, because many of them never presented the scene when defeated doctor leaves the Service ambulance, clinic, emergency room or any other health care area, because the most terrible thing in the profession has happened -the lost of a patient. Sensationalists are rarely present when despair and tears are being replaced by joy, smile and exaltation. They do not understand that it is impossible to meet the doctor who will be prepared to deliberately violate the profession, ethical values, Hippocratic oath, to directly endanger the health or life of the patient, or make a deliberate mistake and commit an offense.